Efficient Solvent‐Free Friedel‐Crafts Benzoylation and Acylation of m‐Xylene Catalyzed by N‐Acetylpyrazine‐2‐carbohydrazide‐Fe(III)‐chloro Complexes. Issue 28 (30th July 2018) - Barman, Tannistha Roy; Sutradhar, Manas; Alegria, Elisabete C. B. A.; Guedes da Silva, M. Fátima C.; Kuznetsov, Maxim L.; Pombeiro, Armando J. L.
Abstract: Reaction of N ‐acetylpyrazine‐2‐carbohydrazide (H2 L) with anhydrous Fe(II) or Fe(III) chloride in CH3 CN or in MeOH leads to the mononuclear [Fe( κ NN'O‐HL)Cl2 ] (1 ) or binuclear [Fe( κ NN'O‐HL)Cl( μ ‐OMe)]2 (2 ) Fe(III) complex, respectively. These complexes are characterized by elemental analysis, ESI‐MS, IR spectroscopy, single‐crystal X‐ray crystallography, electrochemical techniques and DFT calculations. The theoretical calculations indicate that the three single‐electron sequential reductions of1 are centred at the metal, at the pyrazine group and at both, respectively. The catalytic activity of1 and2 was screened towards Friedel‐Crafts benzoylation and acylation of m ‐xylene. The effects of reaction parameters, such as catalyst amount, reaction time and temperature, were studied and, under optimal conditions, 96% yield of 2, 4‐dimethylbenzophenone and 20% yield of 2, 4‐dimethylacetophenone were obtained, respectively. Complex1 exhibited the highest activity in both reactions. The structural and electrochemical properties were supported by theoretical calculations and the importance of the Lewis acid character of the catalyst in the promotion of this catalytic reaction is discussed. Abstract : A mononuclear (1 ) and a binuclear (2 ) Fe(III)‐chloro complexes derived from N ‐acetylpyrazine‐2‐carbohydrazide have been synthesized and characterized by elemental analysis, ESI‐MS, IR spectroscopy, single‐crystal X‐ray crystallography, electrochemical techniques and DFT calculations. The catalytic activity of1 and2 was screened towards Friedel‐Crafts benzoylation and acylation of m ‐xylene. Under optimal conditions, 96% yield of 2, 4‐dimethylbenzophenone and 20% yield of 2, 4‐dimethylacetophenone were obtained by1 . The Lewis acid character of the catalyst in the promotion of this catalytic reaction is discussed.